Background atmospheric conditions of high PM10 concentrations in Istanbul, Turkey - Baltaci, Hakki; Alemdar, Cagla Sinem Ozgen; Akkoyunlu, Bulent Oktay (Turkish Natl Committee Air Pollution Res & Control-Tuncap, 2020)
This study investigates the origin and background atmospheric mechanisms that cause high PM10 concentrations in Istanbul, Turkey. High-PM10 values in Besiktas are defined as days in which the 24-h mean PM10 exceed 100 mu gm(-3) during the period 2007-2017. As a consequence of the application of Ward's minimum clustering technique to HYSPLIT 72 h backward trajectory, mainly four different clusters, which cause high particulate matter episodes, were found in Istanbul. From 94 days, 41.5% of them were categorized as internal sources and are positively (negatively) linked to local temperature (relative humidity) variations. The other sources are shown as external origin and owing to long-range transport of the high particulate matter concentrations; Europe, Russia, and Sahara regions originate 21.3%, 8.5%, and 28.7% of all episodes, respectively. According to the composite analysis of meteorological factors for high PM10 external sources originated by Sahara desert indicates that a strong surface deep low pressure over Italy and an anomalously high pressure over Caspian Sea accompanied by the strong southwesterly wind patterns from Sahara region at mid-levels enable transferring of suspended dust particles to Istanbul in a very short time during spring days. On the other hand, extending of the Azores high-pressure centers from its origin to Balkan Peninsula cause transferring of high-PM10 values by northwesterly flows to Istanbul during winter months. Although high-PM10 episodes originated by Russia shown as least frequent, their contribution to PM10 levels are higher than the other long-range transport pathways. The origins of high-PM10 episodes and their associated meteorological conditions found in this study can provide theoretical underpinnings for dust control strategies and early warnings for health related diseases.
Keywords: PM10; Cluster analysis; Dust; Composite analysis; Istanbul